2021
DOI: 10.1007/s10291-020-01078-8
|View full text |Cite
|
Sign up to set email alerts
|

POD of small LEO satellites based on precise real-time MADOCA and SBAS-aided PPP corrections

Abstract: For real-time precise orbit determination (POD) of low earth orbit (LEO) satellites, high-accuracy global navigation satellite system (GNSS) orbit and clock products are necessary in real-time. Recently, the Japanese multi-GNSS advanced demonstration of orbit and clock analysis (MADOCA) precise point positioning (PPP) service and the new generation of the Australian/New-Zealand satellite-based augmentation system (SBAS) aided PPP service, provide free and precise GNSS products that are directly broadcast throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Precise GPS satellite clock offsets are provided by CODE at a sampling interval of 30 s. Earth rotation parameters are also provided by CODE. Since the precise ephemeris data are provided by CODE every 15 min and the sampling interval of observations is 30 s during orbit determination, it is necessary to interpolate the precise ephemeris data [38]. Bernese 5.2 uses the ninth-order Lagrange interpolation method to interpolate the precise GPS ephemeris data [39].…”
Section: Hy-2c Spacecraftmentioning
confidence: 99%
“…Precise GPS satellite clock offsets are provided by CODE at a sampling interval of 30 s. Earth rotation parameters are also provided by CODE. Since the precise ephemeris data are provided by CODE every 15 min and the sampling interval of observations is 30 s during orbit determination, it is necessary to interpolate the precise ephemeris data [38]. Bernese 5.2 uses the ninth-order Lagrange interpolation method to interpolate the precise GPS ephemeris data [39].…”
Section: Hy-2c Spacecraftmentioning
confidence: 99%
“…Real-time calculation with the EKF method can update the orbital state at a rate of 30 s and the satellite clock error at a rate of 1 s with the latency of 5 s (Takasu, 2013). MADOCA software is employed to provide a Centimeter-Level Augmentation Service (CLAS) by the Japanese Quasi-Zenith Satellite System (QZSS), and the 3D RMS of the real-time GPS orbit error is smaller than 4 cm (Allahvirdi-zadeh et al, 2021;Zhang et al, 2019). The CenterPoint RTX, a global precision real-time service system developed by Trimble, also performs UD decomposition filtering to determine multi-GNSS including GPS, GLONASS, Galileo, QZSS and BDS satellite orbit and clock products in real-time (Leandro et al, 2011;Glocker et al, 2012;Chen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that 7 cm-accuracy kinematic LEO POD can be obtained in real-time mode from the Fugro G4 SSR products based on Swarm-C onboard observations [15]. In addition, the BeiDou navigation satellite system (BDS-3) precise point positioning (PPP) service of China [16,17], the new generation of the Australian/New Zealand (AU/NZ) satellite-based augmentation systems (SBAS)-aided PPP service [18], the Quasi-Zenith Satellite System (QZSS) of Japan [18,19], and Galileo's high-precision PPP service in Europe [20] have their own way to provide real-time GNSS orbit and clock products for users. It is expected that the abovementioned real-time high-precision services will assist spaceborne missions that need precise orbital information.…”
Section: Introductionmentioning
confidence: 99%